Association of routine hematological and inflammation parameters with surgical treatment results in patients with carpal tunnel syndrome - Güneş, Muzaffer (Journal of Surgery and Medicine, 2020)
Aim: Neutrophil/lymphocyte ratio, neutrophil/eosinophil ratio (NER), and C-reactive protein-to-albumin ratio (CAR) reflect systemic inflammation. However, their relationship with the surgical treatment of carpal tunnel syndrome (CTS) has not been studied. In the present research, the association between systemic inflammation parameters and CTS surgical treatment results was investigated in patients with neurophysiologically moderate CTS. Methods: The present study was conducted retrospectively on patients who underwent surgical treatment owing to moderate CTS. The postoperative results were evaluated by a nerve conduction study (NCS) performed approximately 6 months after the surgery. Patients were divided into three groups based on the postoperative NCS: Patients who did not have CTS according to NCS were defined as “the group fully benefiting” from surgical treatment, patients with mild CTS were included in “the group partially benefiting,” from surgical treatment, and patients with moderate or severe CTS were included in “the group with no benefit.” Results: Forty-one patients with moderate CTS were included in the study. There was a significant difference between the groups in terms of median CAR, white blood cell, neutrophil, NER, and C-reactive protein (CRP) levels (P<0.001, P=0.012, P=0.014, P=0.005 and P=0.001, respectively). There was also a statistically significant and strong positive correlation among postoperative CTS severity, CAR (rho: 0.633, P<0.001) and CRP (rho: 0.603, P<0.001). Conclusion: In the current study, it was found that CTS patients with higher CAR levels achieved less benefit from the surgical treatment.